Influence of doping chromium ions on the electrical properties of hydroxyapatite. Issue 1 (1st January 2020) - Ibrahim, Moustafa; Dawood, Abdelfattah
ABSTRACT: Hydroxyapatite Ca10 [PO4 ]6 [OH] is a biocompatible widely used in medicine and dentistry. Its applications depend greatly upon lattice substitution of Calcium sites in its structure by varies cations such as Na, Mg, Sr, Ag etc. Chromium plays an important role in reducing blood sugar level and improving insulin ability to convert glucose in cells to gain energy. In this paper we studied the effect of doping hydroxyapatite with chromium ions on its crystal dielectric properties. Pure hydroxyapatite and chromium loaded hydroxyapatite of chromium concentrations of 0.5, 1.0, 2.0, and 3.0 wt % forming samples S1, S2, S3 and S4 respectively were prepared by wet precipitation method. The dielectric parameters, permittivity ἐ, dielectric loss ἕ, conductivity σ, relaxation time ts and dielectric modulus M' and M'' were calculated at frequency of 20 Hz to 10 MHz. Results showed increase of ἐ, and ἕ, values of chromium loaded samples compared to pure hydroxyapatite. The conductivity of the doped samples was increased with chromium concentration increase. The relaxation times (ts ) chromium loaded samples showed increase of ts as chromium concentration increase. The dielectric properties showed that as chromium concentration increase, ἐ, ἕ, and σ of substance increase compared to the pure HA.